Parasitological studies on agama lizard (agama agama) in Ibadan (2011)
The parasitological studies of agama lizard (Agama agama) in Ibadan was carried out by selectively picking sixty growing agama lizards of lengths ranging from 22.9cm to 37.5cm (snout-vent length), from five local governments in Ibadan, Oyo state, Nigeria. The lizards were dissected for the collection of the worms which were found in the stomach, intestine and rectum. The worms were identified with a microscope. Parasitological variables were presented on tables and summarized as percentages. Strongyluris brevicaudata and Thelandros annulatus were the prevalent parasites. Across the five local governments, Strongyluris brevicaudata had the highest infection rate in Ibadan South East (87.50%) while Thelandros annulatus was highest in Ibadan North (75.86%). The prevalence of infection of Strongyluris brevicaudata was higher than Thelandros annulatus. The entire male and female specimens examined were found to be parasitized. Females had higher intensity of infection in Ibadan North (51.72%), South east (54.68%) and North west (53.57%) while the male had the highest infection rate in only two local governments, Ibadan North East (48.44%) and Ibadan South West (49.15%).